Analysis of the service of volleyball in female juvenile category in terms of level risk assumed and his efficacy - J. V. García-Tormo; J. C. Redondo; J. A. Valladares; J. C. Morante (Asociación Española de Ciencias del Deporte, 2010)
The service, one of the more important actions in volleyball has been conditioned by the experienced evolution by this sport over the past decades, what has brought important changes in the execution of the technique of the service just as in the tactical systems used by the teams. According to an observational model, a methodological proposal developed in five phases has ensued for analysis and assessment of the level of risk that they assume them players of volleyball in juvenile category in the service regarding the obtained efficacy. In that one methodology has been identified and established the variables that affect it, stops at a later time quantifying and examining the level of risk in terms of the kind of service and of the trajectory described all by himself. The obtained data (2.237 cases) were examined statistically to come to an end that this category does not appraise a command and control itself enough as if to evidence a tactical obvious intentionality that players would assume a voluntary risk level and once the situation was adapted of the match. KEY WORDS: volleyball, service, risk level, efficacy.